Pathogen discovery in the respiratory tract - van Doorn, H. Rogier (Henry Stewart Talks, 2013)
Pathogen discovery in the respiratory tract, An overview of recently discovered viruses in the respiratory tract, Techniques for directed and agnostic viral detection, From nucleic acid sequence to proof of disease causation